Facile formation with HA/Sr-GO-based composite coatings via green hydrothermal treatment on ?-type TiNbTaZr alloys: Morphological and electrochemical insights - Yigit, Oktay; Dikici, Burak; Kaseem, Mosab; Nakai, Masaaki; Niinomi, Mitsuo (Springer Heidelberg, 2022)
This work looked into the formation of a hybrid composite coating composed of strontium-doped hydroxyapatite (HA) and graphene oxide (GO) on the surface of beta-type TiNbTaZr (TNTZ) alloy via a green hydrothermal method. To achieve this goal, various GO concentrations, 1.5, 3.0, and 4.5 wt%, were added to autoclave linked solution. The inclusion of GO led to a reduction in the crystallinity of HA/Sr coating where dense homogenous rods nanocrystalline structures were observed in the case of 4.5 wt% of GO. Furthermore, per electrochemical measurements in a simulated body fluid (SBF) solution, it was found that the composite coating was made from a solution with 4.5 wt% GO which had the lowest corrosion density of 83 nA cm(-2) with the highest polarization resistance (237,415 Omega cm(2)). The results showed that the hydrophilic HA/Sr-GO composite coatings prepared in the present work can be used as a potential candidate in orthopedic applications.
Keywords: In-Situ Synthesis; Plasma Electrolytic Oxidation; Layered Double Hydroxide; Graphene Oxide; Drug-Delivery; Corrosion-Resistance; Titanium-Alloys; Hydroxyapatite; Strontium; Deposition